Increasing of CIR Performance of the OFDM System without Increasing Hardware Complexity (International Journal of Engineering and Computer Science, 2015)
Symmetric symbol repeat (SSR) inter carrier interference (ICI) self cancellation scheme has proved to be a simple and convenient technique to reduce ICI caused by frequency offsets. It utilizes data allocation and combining of    (1,-1) on two symmetrically placed subcarriers to mitigate the effect of ICI. However, the data allocation factors (1,-1) are not an optimum. In this paper, an optimum data allocation (1, -